The Effect of Managerial Intentions and Initiatives on Green Supply Chain Management (GrSCM) Application and the Performance of Manufacturing Companies in Indonesia - Syafrida Hafni Sahir (Politeknik APP Jakarta, 2022)
This study aims to determine the effect of managerial intentions and initiatives on Green supply chain management (GrSCM) application. This study also investigates the effect of GrSCM and inter-company trust on firm performance. This study used quantitative methods. The determination of the sample used purposive sampling techniques involving 91 manufacturing companies in Indonesia. Data were analyzed using descriptive and inter-correlation analysis with the help of SPSS and SmartPLS software. The results of this study indicated that the initiative has a positive and significant effect on GrSCM application, while the intention has no significant effect on GrSCM application. The implementation of GrSCM showed a low significant relationship to company performance. Besides, the initiative variable could not moderate the implementation of GrSCM, while trust could moderate the effect of GrSCM application on company performance.